Pengaruh Citra Merek, Kualitas Produk dan Harga terhadap Keputusan Pembelian pada Produk Korek Api Gas Tokai di Surabaya - Akbar, Achmad Muktafi; Iriani, Sri Setyo (Peneliti.net, 2025)
A purchasing decision is the process by which consumers choose to purchase a particular product or service after evaluating various factors that influence their choice. This research aims to determine the influence of brand image, product quality and price on purchasing decisions for Tokai gas lighter products in Surabaya. The type of data used is quantitative data using non-probability sampling techniques. Data was collected using a purposive sampling method with 200 samples. Data were analyzed using multiple linear regression and calculated using IBM SPSS 25. The results of this research show that the variables of product quality, brand image and price have a positive influence on purchasing decisions. Product quality, brand image, and price simultaneously influence purchasing decisions about Tokai gas lighters. The practical implications of these findings are the importance of improving product quality, by ensuring products have good durability, high efficiency, and superior safety features, companies can increase consumer trust and loyalty, set competitive prices, and build and maintain a strong brand image. strong to increase consumer trust and loyalty. Building and maintaining a strong brand image is the key to attracting and retaining customers. Keywords: brand image; price; product quality; purchasing decisions.